International economic / Dominick Salvatore - Salvatore, Dominick
"This is the 13th edition of a text that has enjoyed a flattering market success, having been adopted by more than 700 colleges and universities throughout the United States, Canada, and other English-speaking countries. The text has also been translated into Chinese, French, Greek, Indonesian, Italian, Korean, Polish, Portuguese (Brazilian), Serbian, Spanish, Russian, and other languages. All of the features that have made the previous editions of this text, one of the leading texts of International Economics in the United States and around the world, have been retained in the 12th edition. However, the content has been thoroughly updated and expanded to include many new significant topics and important recent developments"